Thermal design of a shell-and-tube heat exchanger for methanol cooling (Nexo Revista Científica, 2020)
The heat transfer between fluids is an essential part of most chemical processes. In this work the thermal design of a shell-and-tube heat exchanger was carried out to cool a methanol stream from 60 to 30 °C, using water at 5 °C as a cooling agent. The designed equipment will have a shell diameter of 0.39 m, a tube pitch of 0.0254 m, a baffle number of 26, a baffle spacing of 0.186 m, a number of tubes of 124, a surface over design (OS) of 26.25% and a calculated length (LC) of 3.71 m. The calculated pressure drops were 3,972.93 Pa and 3,099.59 Pa for water and methanol, respectively. The designed shell and tube heat exchanger is suitable for the service required, since the OS does not exceed 40%; it is true that Lc < LT; and the calculated values ​​of the pressure drops are not greater than the maximum allowable pressure drop for both streams. Finally, the designed equipment will have a preliminary cost of USD $ 41,800.